Analisis Kesulitan Siswa Dalam Pembelajaran Matematika dan Upaya Mengatasinya di Kelas IV SD Negeri Gunung Bunder 05 - Siti Rizki Mahwiyah; Chaira Sadiah; Ernawati Humaira (EduInovasi: Journal of Basic Educational Studies, 2023)
Mathematics is one of the subjects taught at various levels of education from elementary school to high school level. Based on observations, it was found that students had difficulties in mathematics. The problem is related to the learning system so that students have difficulty working on questions and making mistakes is one factor. Another difficulty is the lack of learning media, learning variations and low learning outcomes so that they do not exceed the learning objectives taught by the teacher. This study aims to determine the analysis of students' difficulties in learning mathematics and efforts to overcome them in the fourth grade of SD Negeri Gunung Bunder 05. The type of research used is a field qualitative research method that collects data using interview and documentation techniques. The subjects of this study were class IV and class IV guardians at SD Negeri Gunung Bunder 05. Based on the results of the research and discussion, it was concluded that there were several teaching preparations prepared by the fourth grade homeroom teacher, namely preparing several learning administrations, one example of which was preparing the latest model lesson plans for elementary school teachers using lesson plans and thematic syllabus where each subject was themed. The implementation of the mathematics learning process in grade IV includes approaches, strategies and learning methods that are applied to student activities. This can be seen from the approach used by the teacher, namely the behavioral approach (behavior therapy), an approach to learning activities that emphasizes behavioral theory as an application of behaviorism theory. The strategy used by the teacher in learning mathematics is a learning strategy that is oriented to student activities. The method applied by the teacher is to combine several methods, namely the lecture method, question and answer, discussion, cooperative learning groups and exercises whose use emphasizes student activities by using different learning methods and strategies, so the learning process in class will have a different atmosphere with finally the material being taught. and learning objectives will be delivered properly. Keywords: Students' Difficulty, Mathematics Subjects, Efforts to Overcome.